Political economy of China and US value chains in Latin America (Journal of Business, Universidad del Pacífico (Lima, Peru), 2023)
In this paper, I aim to provide empirical evidence about how an efficient integration into global value chains can promote economic growth through industrial upgrading and prevention of external imbalances in Latin America (LATAM). I define US-China political economics in this region for the period from 1998 to 2015. The research uses TiVA raw data that I obtained from the UNCTAD-EORA database for the US, China, and nine major economies in LATAM. The development of global value chains has brought unprecedented alternatives for commercial alliances and industrial strategies to developing countries. An effective integration of LATAM onto global value chains through forward linkages or increases in indirect value added (DVX) can strengthen both their industrial development and manufacturing industries to achieve the macroeconomic goal of long-term economic growth. China as the world’s fastest growing economy when trade is measured by the value added has stimulated forward linkages and economic development throughout several developing countries within the ASEAN+3, EU -13, and LATAM since 1998. However, strategic competition with the US has prevented China from further expanding its value chain to LATAM. Therefore, the whole region endures a peripherical position in relation to global value chains, as it is still too reliant on lower value-added investments in extractive industries. Yet strengthening TiVA exchanges with China, along with the US, is critical to broadening the alternatives for a sound and sustainable economic development in LATAM.